Mapping the Financial Risk Management Landscape: A Bibliometric Analysis of Recent Trends and Influential Contributions - Loso Judijanto; Antoni Antoni; Evracia Turukay; Hasmia Melati Arifin (Westscience Press, 2023)
This bibliometric analysis explores recent trends and influential contributions in financial risk management, shedding light on thematic clusters, keyword occurrences, and highly cited works. The analysis encompasses a wide array of literature, ranging from the integration of risk considerations into broader corporate strategies to the impact of technological advancements on risk management practices. Thematic clusters reveal the interconnectedness of business practices, corporate social responsibility, and risk management, while keyword occurrences highlight dominant themes like financial performance and credit risk management. Highly cited works by notable authors provide foundational insights into risk management for financial institutions, emphasizing liquidity risk, corporate governance, and the integration of theoretical frameworks with practical applications. The synthesis of these findings offers a comprehensive understanding of the evolving landscape of financial risk management, guiding researchers, practitioners, and policymakers in navigating the complexities of risk in contemporary financial contexts.